Catecholaminergic stimulation restores high-sucrose diet-induced hippocampal dysfunction. (May 2021) - Hernández-Ramírez, Susana; Osorio-Gómez, Daniel; Escobar, Martha L.; Rodríguez-Durán, Luis; Velasco, Myrian; Bermúdez-Rattoni, Federico; Hiriart, Marcia; Guzmán-Ramos, Kioko R.
Abstract: Increasing evidence suggests that long-term consumption of high-caloric diets increases the risk of developing cognitive dysfunctions. In the present study, we assessed the catecholaminergic activity in the hippocampus as a modulatory mechanism that is altered in rats exposed to six months of a high-sucrose diet (HSD). Male Wistar rats fed with this diet developed a metabolic disorder and showed impaired spatial memory in both water maze and object location memory (OLM) tasks. Intrahippocampal free-movement microdialysis showed a diminished dopaminergic and noradrenergic response to object exploration during OLM acquisition compared to rats fed with normal diet. In addition, electrophysiological results revealed an impaired long-term potentiation (LTP) of the perforant to dentate gyrus pathway in rats exposed to a HSD. Local administration of nomifensine, a catecholaminergic reuptake inhibitor, prior to OLM acquisition or LTP induction, improved long-term memory and electrophysiological responses, respectively. These results suggest that chronic exposure to HSD induces a hippocampal deterioration which impacts on cognitive and neural plasticity events negatively; these impairments can be ameliorated by increasing or restituting the affected catecholaminergic activity. Highlights: Chronic consumption of high-sucrose diet impairs hippocampus dependent memories. In vivo long-term potentiation of the perforant path to dentate gyrus is affected. Hippocampal catecholaminergic response to object is decreased. Blockade of catecholamine reuptake restitutes synaptic efficiency alterations. Blockade of catecholamine reuptake improves diet-induced cognitive impairment.